Business Development of Dental Services Marketing in Hospital: A Systematic Review - Ekasari, Ferti Dwi; Sulistiadi, Wahyu (UI Scholars Hub, 2020)
One of the health services in the hospital is dental and oral health care. Hospitals must establish a good marketing strategy for their organizations in an effort to continue to improve or maintain the expected position. Based on the above, it is necessary to know what efforts can be made by dental outpatient clinics in developing marketing of dental and oral health services in dental clinics in hospitals to increase patient visits to hospital dental clinics. This study use Systematic Review with PRISMA method retrieved from online database such as ProQuest, willy online, J Store, Scopus and Google Schoolars using a keyword “Dental services